Pengaruh Shalat Tahajud (Qiyamullail) Terhadap Penurunan Tekanan Darah Pada Pasien Dengan Terapi Antihipertensi Di Puskesmas Tlogosari Kulon - Fathnin, Fildza Huwaina; Sugiyanti; Annidasari, Hadika (Sultan Agung Islamic University of Semarang, 2025)
Background: Hypertension is a condition in which systolic blood pressure exceeds 140 mmHg and diastolic more than 90 mmHg. Indicators that can cause hypertension are emotional and mental conditions, which affect a person's stress levels. To manage hypertension, a step that can be taken is self-meditation, one of which is by performing tahajud prayer (qiyamullail). Tahajud prayer is believed to help reduce stress and play a role in lowering blood pressure. The purpose of this study is to determine the effect of tahajud prayer (qiyamullail) on lowering blood pressure in hypertensive patients at the Puskesmas Tlogosari Kulon. Methods: This study adopted a quantitative method with a cross-sectional research design, where data were collected using a questionnaire. Samples were taken by simple random selection, involving 32 participants, and data were analyzed using univariate and bivariate analysis. Results: Based on the results of the correlation test using spearman correlation in the table above, the frequency affects systolic changes with the value of sig. 0.007 which means that it has a moderate relationship because the sig value is <0.05. The relationship between understanding and systolic and diastolic changes and frequency with diastolic changes is said to have no significant relationship because the sig value is >0.05. Conclusion: Frequency affects systolic changes significantly, which can be seen from the results of the sociifikan value obtained from the Asymp value. Sig < 0.05 which is 0.007.